Hepatic epithelioid angiomyolipoma: a case report - Logrado, Ana; Pereira, Raquel; Constantino, Júlio; Sá, Milene; Pereira, Jorge; Oliveira, Rui C.; Casimiro, Carlos (International Surgery Journal, 2021)
Angiomyolipoma (AML) is a rare benign solid tumor, of mesenchymal origin. Angiomyolipomas can be subdivided, according to their predominant component. The predominance of epithelioid cells characterizes the epithelioid variant (EAML). These express a more aggressive clinical behaviour with a greater potential for malignant transformation. In the absence of specific radiological features, the diagnosis of hepatic EAML depends on the pathological and immunohistochemical study. We present the case of an 80 years old female with a computed tomography (CT) scan showing a hepatic nodule at the transition of segments 5 and 8, and a left kidney nodule previously biopsied and confirmed to be a renal angiomyolipoma. A liver nodule biopsy was performed, whose histology revealed a probable gastrointestinal stromal tumor (GIST). The patient underwent a 5/8 subsegmentectomy and pathology report revealed epithelioid angiomyolipoma. After discussion of the case in the multidisciplinary tumor board, it was decided to perform a left nephrectomy, whose pathology revealed leiomyomatous angiomyolipoma. No further treatment and surveillance on outpatient clinic were decided. Hepatic EAML is a rare lesion that, although mostly benign, can exhibit malignant behavior with distant metastasis and local invasion. Its identification is of paramount importance. The definitive diagnosis is only possible through histological and immunohistochemical analysis. Additional studies are needed in order to establish diagnostic criteria and predictive characteristics of malignancy.